The influence of psychological capital on employment expectations of vocational undergraduate students: The chain mediating role of active coping style and educational flow experience - Zerui Huang; Ismi Arif Ismail; Akmar Hayati Ahmad Ghazali; Jeffrey Lawrence D’Silva; Haslinda Abdullah; Zeqing Zhang (PLoS ONE, 2025)
As vocational undergraduate students in China face increasing challenges in the job market, understanding the factors that shape their employment expectations is crucial. Psychological capital is considered a key factor influencing students’ career outlooks. This study aims to examine the relationship between psychological capital (PC) and employment expectations (EE), while exploring the mediating roles of educational flow experience (EFE) and active coping style (ACS) in this relationship. Based on positive psychology and career development theories, a theoretical model was constructed to understand how psychological capital affects employment expectations through the chain mediation of educational flow experience and active coping style. A sample of 693 vocational undergraduate students (316 males and 377 females) from a university in Guangdong Province participated in the study. Participants completed the Psychological Capital Scale (PCS), the Career Expectation Scale (CES), the Educational Flow Experience Scale (EduFlow-2), and the Coping Style Scale (CSS). Results indicate that higher levels of psychological capital significantly predict stronger employment expectations. Moreover, educational flow experience and active coping style both serve as significant mediators in the relationship between psychological capital and employment expectations, with a chain mediation effect also observed. These findings provide valuable insights into the psychological processes that influence career expectations among vocational undergraduates, highlighting the importance of fostering psychological capital and creating supportive learning environments to improve students’ employability. The results offer practical implications for educators and policymakers, suggesting that vocational institutions should integrate strategies to enhance psychological capital, promote educational flow experiences, and support active coping styles to better prepare students for the labor market.